Europäischer Handel mit Treibhausgasemissionszertifikaten und seine Umsetzung in das deutsche Umweltrecht - Fritz Rahmeyer (Universität Augsburg, Institut für Volkswirtschaftslehre, 2007)
With coming into force of the Directive 2003/87/EU of the European Parliament and of the Council greenhouse gas emission allowance trading within the community (EU ETS) has begun in 2005. Emission trading is a flexible instrument to abate emissions within the framework of the Kyoto-Protocol. Up to this time command-and-control regulations and national emission or energy taxes were predominant within environmental policy. The German Pollution Protection Law (Bundesimmissionsschutzgesetz) and emission trading were incompatible. As a result the EU-Directive released approved industrial installations, which take part in emission allowance trading, from fulfilling their duty to keep marginal emission values. It is the purpose of this paper to present and elucidate the sectoral system of emission allowance trading according to the EU-Directive and its legal consequences. To start with integral parts of the science and the economics of climate change are subjects under debate. In particular the discounting of future damage costs is looked at. After that the political architecture of climate-change policy and its instruments is dealt with in detail. In the following the broadening of the established German Pollution Protection Law with regard to the EU-Directive is in the fore, besides that the national rules of allocation of EU emission allowances to entitled enterprises.
urn:nbn:de:bvb:384-opus4-711387
Keywords: Q54; Q58; 330; Climate policy; emission trading; environmental law; national allocation plan; Emissionshandel; EU-Umweltrecht; Immissionsschutz; Allokation; Deutschland